Land grants in the jurisdiction of the city of Concepción, Chile (1550-1599) - Stewart, Daniel; Urbina, Simón; Adán, Leonor (Revista Chilena de Antropología, 2023)
This article deals with the modality of territorial colonization and conformation of land ownership around the city of Concepción starting in 1550. The process of assigning encomiendas and different types of land grants is documented, analyzing unpublished data from Hispanic and mapuche agents who participated, negotiated, and implemented the Spanish legal frameworks during this period. Parallel processes have been verified in connection to the founding of other cities in the southern center of the Chilean territory. The article provides a first sequence of construction of colonial territoriality around the city of Concepción, distinguishing the legal instruments used by different local government entities (town council), governors, religious, neighbors and mapuche political authorities and representatives of the King, and its concrete geographic-spatial expression.